(untitled) (Eurasian Journal of Philology Science and Education, 2016)
Spirituality can be defined as the feeling and understanding by a man of own unity, own inextricable connection with the surrounding world. We distinguish two levels of spirituality in this definition – feeling and awareness and believe that uneducated man, intuitively sensing the equivalence and the inextricable connection of own self and the rest of the world can be spiritual either. These people build their relationship with the world based not on fear or coercion, but on love, empathy and compassion. On the level of awareness spirituality is attained when a person synthesizes all knowledge about the world and penetrates into the essence of the deep relationships of all its manifestations in the process of upbringing, education and self-education. The definition of spirituality would be incomplete without mentioning the faith in divine unity of all things. The role of religion, its importance in regulating the morality of a person is significant in the transition period of his development. When the feeling is not sufficient for moral self-regulation, and understanding of the unity of the world is not yet achieved or unachievable due to life circumstances, faith is the only source that can help a person to establish a truly humane relationship with the world.